Drivers of egovernment adoption amidst COVID-19 pandemic: The Information Adoption Model (IAM) approach. (November 2022) - Mensah, Isaac Kofi; Adams, Samuel; Adjei, Joseph Kwame; Mwakapesa, Deborah Simon
The study scrutinized the behavioral adoption of informational e-government services among Chinese citizens in the midst of the COVID-19 pandemic. A structural equation modeling (SEM) technique was applied for the data analysis using Smart PLS 3.0 statistical software. The results show that information quality, information credibility, and ease of COVID-19 informational e-government services are significant in determining citizens' perception of the usefulness of COVID-19 information shared on e-government platforms. Also, the study revealed that the perceived usefulness of COVID-19 informational e-government services was significant in predicting citizens' intention to adopt and recommend COVID-19 informational e-government services. The theoretical and practical implications of these findings are interrogated further.